Firm size as a moderator in the relationship between board characteristics and financial performance in sri lanka - Tharsika, K.; Thaneshan, G.; Varanitha, S. (University of Jaffna, 2024)
Despite extensive scholarly work on the association between board characteristics and financial performance, the moderating effect of firm size on this link remains unexplored. Thus, this study aims to determine the moderating role of firm size in the relationship between board characteristics and financial performance in a developing nation, Sri Lanka. The study uses the panel data from 100 non-financial listed companies in the Colombo Stock Exchange from 2019 to 2023, and financial performance as assessed via Return on Assets (ROA) and board characteristics, including board size, independence, and board meetings. The Hausman and Breusch-Pagan Lagrangian multiplier tests indicate that the random effects model is more suitable than the fixed effects or pooled ordinary least squares models. Findings reveal that firm size, as a moderating variable, negatively impacts the relationship between board size and ROA, while it does not significantly influence the links between board independence or board meetings and ROA. The limitations is that it focuses on a five-year period and considers only specific board characteristics variables, while using ROA as the sole measure of performance. This scope may restrict the generalizability of findings to broader governance frameworks or performance indicators. Nevertheless, the study contributes empirical evidence to the limited research on the role of firm size in board characteristics and performance dynamics in Sri Lanka. The findings provide practical insights for managers, legislators, and regulators to design board structure that incorporates firm size considerations. By addressing this research gap, the study enhances understanding of board governance in emerging economies.
Keywords: Board Characteristics; Colombo Stock Exchange; Financial Performance; Non-financial Listed Companies